Perspective and review: how to develop our understanding of temporal changes in the relationship between people and the landscape under societal and climate change in Northeast Asia? - Shin, Nagai; Saitoh, Taku M.; Kotani, Ayumi; Miura, Tomoaki; Nakagawa, Hiromi; Katsumata, Chifuyu; Morimoto, Hiroshi; Onishi, Hideyuki (Frontiers in Environmental Science, 2024)
The relationship between people and the landscape consists of multi-layer components such as the atmosphere, water, living things, nutrients, livelihood, society, and information. To clarify temporal changes in this relationship, previous studies have used conventional approaches based on field work and satellite observation. However, interpretations based on these conventional two approaches are subject to temporal, spatial, representative, and interpretability gaps. In this perspective and review paper, we propose three approaches to bridge these gaps: (1) text mining of historical documents and data (mining for handwritten or printed old documents, books, diaries, field notes, and statistics), (2) video mining (mining for descriptions, interviews, narrations, and background of photos/video), and (3) social sensing (observing real-world events by using digital communication tools such as social networking services, YouTube, and Google Trends). We discuss the utility, limitation, and perspective of each of these proposed approaches by presenting case examples of their application from Northeast Asia. We found that (1) the text mining approach can be useful to remove the temporal, representative, and interpretability gaps but requires immense amounts of time and labor;(2) the video mining approach can be useful to remove the temporal, representative, and interpretability gaps, but uncertainties remain and there are usage limitations with video materials; and (3) the social sensing approach can be useful to reduce the spatial, representative, and interpretability gaps, but it requires careful consideration in terms of data quality and ethical issues. To deepen our understanding of the relationship between people and the landscape during periods of social and climate change on a scale of seasons to centuries from the viewpoint of personal attributes and traits, we conclude that an integrated analysis that combines the conventional approaches such as field work and satellite observation and the proposed approaches should be further developed. Through the development of our proposed integrated analytical approaches, we expect to establish a new transdisciplinary study that integrates anthropology, sociology, informatics, history, and natural sciences.